High Percentage of Evanescent Red Cell Antibodies in Patients with Sickle Cell Disease Highlights Need for a National Antibody Database. Issue 9 (September 2016) - Williams, Lance A.; Lorenz, Robin G.; Tahir, Absar; Pham, Huy P.; Marques, Marisa B.
Abstract : Objectives: Alloantibody formation secondary to transfusion in patients with sickle cell disease (SCD) is a well-known phenomenon. Pretransfusion testing (eg, "antibody screening") protects patients from receiving incompatible red blood cell transfusions. Because alloantibodies have a tendency to evanesce (ie, become undetectable over time), however, this phenomenon puts patients at risk of a delayed hemolytic transfusion reaction or even acute hemolysis. Methods: We evaluated the records of 71 patients with SCD with alloantibodies detected during a 2-year period to describe their most common specificities and their rate of evanescence. Results: We found that 81% of patients had at least one antibody that was undetectable during the study period; therefore, if patients were transfused with antigen-positive units at a facility that was unaware of their antibody history, life-threatening hemolysis could develop. Conclusions: Evanescence is a real risk for patients with SCD, and national/regional databases of alloantibodies should be considered a priority. Abstract : Alloantibody formation in response to blood transfusion occurs not uncommonly in patients with sickle cell disease (SCD). Over time, such antibodies may "evanesce" or disappear, leaving patients at risk of hemolytic transfusion reactions during their next transfusion. The authors found a high percentage of evanescence in their SCD population and describe the reasons why there is a great need for a national or regional alloantibody database, especially for this patient population.